Smart Buyer Generation: Cara Mengendalikan Diri dari Impulsive Buying di Era E-Commerce - Budi Prasetiyo; Faqih Ahmad Muzakky (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The development of digital technology and the growth of e-commerce in Indonesia have driven changes in consumer behavior patterns, particularly among adolescents as the digital native generation. The ease of access to online shopping platforms, time-limited promotions such as flash sales, digital payment systems, and paylater features have the potential to increase the tendency toward impulsive buying among school-aged youth. This condition raises concern because weak self-control and low financial literacy can lead to unplanned and risky consumptive behavior in the future. This community service program, titled "Smart Buyer Generation: Strategies for Self-Control against Impulsive Buying in the E-Commerce Era," was implemented among students of Darul Hikam Integrated School Secondary (DHIS Secondary) - Lodaya as the target community. The activity aims to enhance conceptual understanding of impulsive buying behavior, strengthen the ability to distinguish between needs and wants, and develop self-regulation skills in purchasing decisions. The implementation method was conducted participatively through preparation stages, initial assessment, delivery of financial literacy and digital consumer behavior materials, case simulations, interactive discussions, and evaluation through pre-test and post-test. The educational approach was designed not only to be informative but also reflective and applicative, enabling participants to internalize the values of rational and responsible consumption. The expected outcomes include increased critical awareness of digital marketing strategies, the formation of a smart buyer mindset, and the creation of change agents within the school environment capable of disseminating wise consumption practices. This program also aligns with the scientific roadmap that emphasizes the strengthening of economy and human resources in the digital era, thus possessing sustainability potential in the form of developing digital financial literacy modules for adolescents.